Cross-frequency coupling of frontal theta and posterior alpha is unrelated to the fidelity of visual long-term memory encoding. Issue 6 (3rd July 2022) - Zhao, Chong; Fukuda, Keisuke; Woodman, Geoffrey F.
ABSTRACT: Because visual long-term memory relies on multiple spatially distinct brain areas, encoding representations is likely to rely on networks formed via large-scale coupled neuronal oscillations. Decreases in occipital alpha power and increases in mid-frontal theta power appear to individually contribute to the encoding of visual long-term memories. Here we ask whether these oscillations form a coupled network. We show that neither amplitude-amplitude nor phase-amplitude coupling between frontal theta and posterior alpha are related to observers' subsequent memory. Correlations between alpha and theta power were stronger during eyes-open, resting-state periods than immediately following the presentation of a to-be-remembered picture. Finally, we found that the strength of theta-alpha coupling was not modified by temporal lobe anodal transcranial direct current stimulation, despite performance showing enhanced memory. These findings indicate that posterior alpha and frontal theta activity are not simply component parts of a larger scale coupled network underlying visual memory.